What Does School Attendance Mean in Japanese Compulsory Education Schools? Analysing the National Annual Report - Naoki Maeda (Karolinum Press, 2023)
School absenteeism in Japan has become a serious psychosocial issue over the past few decades. According to the national survey conducted annually by the Ministry of Education, Culture, Sports, Science and Technology − Japan (MEXT), the number of students with school attendance problems (futoko) in compulsory education schools has been the highest since the government introduced the current data collection format in 1991. All Japanese compulsory education schools collect data on attendance and absence each day. The obtained data in each school are collected by MEXT via local education boards, which are eventually reported as annual national data. However, in recent years, data classification and interpretation of school attendance and absenteeism have become more complicated, which may constitute a limiting factor for appropriate measures for school absenteeism in Japan. The current study showed the situation of school absenteeism in Japanese compulsory education schools using the annual data reported by MEXT, and it examined matters of data classification and interpretation. The author proposed that two main categories of attendance/absence be used, namely: (a) class attendance in mainstream schools, and (b) class nonattendance in mainstream schools.